Exploring reduced global standards-based inter-organisational information technology adoption. Issue 11 (2nd November 2015) - Power, Damien; Gruner, Richard L.
Abstract : Purpose: – The information technology (IT) literature is mixed regarding the benefits of inter-organisational IT, but shifts towards less adoption of IT remain largely an unexplored area of research. The purpose of this paper is to address this gap by shedding light on the question of whether or not such shifts exist, and if so, why they occur. Design/methodology/approach: – A mixed method, sequential research design was adopted. A quantitative study based on two cross-sectional surveys conducted in 2001 and 2011 yielded responses from 62 matching firms that had implemented IT based on global GS1 standards. Survey results led to the identification of a group of organisations that provided evidence of reduced standards-based inter-organisation IT over time. Subsequently, four theory-building in-depth case studies explored why changes towards less IT occurred. Findings: – Results from the quantitative study show that measurable changes take place in IT implementation over time (both increasing and decreasing). The case studies show that changes towards less implementation of IT are largely explained by a complex interaction of multiple factors lending support to a situational model of IT adoption. Research limitations/implications: – The empirical investigations were limited to Australian manufacturers. Further studies should extend the generalisability of the findings and study the phenomenon in different contexts, as well as across firms that increased, decreased, and maintained their level of IT over time. Practical implications: – The study helps managers to identify the IT that best suits their strategic objectives. Further, this research increases managers' understanding of how to better use IT as firms weigh opportunities to invest in new supply chain technologies and as a result may choose to reduce investment as a strategic alternative. Originality/value: – The paper provides the first systematic insight into reduced IT standards use and implementation. The authors offer a more granular understanding of why firms may choose to reduce usage of IT over time.